Stabilization of Sludge in Zakho Municipal Wastewater by Anaerobic Digestion for Biogas Production in Kurdistan Region, Iraq - Tamar, Shreen Abdulkareem; Umer, Mustafa Ismail (Science Journal of University of Zakho, 2022)
Raw wastewater sludge samples were collected from two sanitary point sources in Zakho city wastewater pipes. Anaerobic digestion is utilized sludge stabilization as it was effective in reducing the volume of sludge and cheap source of clean biogas. the sludge of municipal wastewater of Zakho district is worth to be used for the generation of biogas and just 15 -17 kg sludge produced 233 to 350 m3 gas in solid retention time of 18 and 24 day respectively. Suspended solid is close related to the amount of COD that removed from sludge and approximately 1 kg COD generate 0.5-0.55 Kg suspended solid in the water. Volatile solid (VS) /total solid (TS) ratio is 0.46 after anaerobic digestion which locate in the range of anaerobic lagoon stabilization. Anaerobic digestion lead to reduction in total solid of wastewater especially organic or volatile suspended solid. Specific gravity of the sludge solid is1.5 which indicate that the sludge is stabilized by anaerobic digestion. Sludge volume index (SVI) indicate that the settleable biosolids are old, good quality and low turbidity. Sludge density index (SDI) increased from 1.83 to 2.9 ml/g after stabilization by anerobic digestion. CO2 and H2S are reduced to zero after stabilization by anaerobic digestion. Nutrients N, P, Ca, Mg, Cl are elevated significantly in final stabilized sludge to be used as organic fertilizer, except sulfate is decreased to acceptable ranges after stabilization.